Pregnant women are doing it for themselves: Self-monitoring of blood pressure in pregnancy - Lavallee, L; Tucker, K; McManus, R (Mark Allen Healthcare, 2018)
Regular blood pressure checks are crucial to the early detection of pre-eclampsia and are associated with better maternal and neonatal outcomes. Hypertension can develop between antenatal visits, however, and complications may progress rapidly. Having women monitor their own blood pressure at home could be an effective way of overcoming this problem, providing a cost-effective means to improve outcomes and empower women. Further evidence is needed, however, to ensure that the practice is implemented safely and favourably for both women and health professionals.